MEDICOSURGICAL MANAGEMENT OF SUB-CUTANEOUS FIBRO PAPILLOMA IN A MALE BUFFALO CALF - Jana, Debasis; Ghosh , Mousumi (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Bovine Papilloma Virus (BPV) has been found to induce both fibroblastic as well as epithelial cell response for the development of cutaneous and or sub-cutaneous fibropapillomatosis both in cattle and buffaloes. Although cutaneous papillomatosis is very common in bovines, subcutaneous fibropapillomatosis is virtually very uncommon in buffaloes. Present communication reports a very rare incidence of subcutaneous fibropapillomatosis in a young male buffalo and its successful medico-surgical management.